Utilization of the “Horse Whip” Plant Into Processed Health Drinks for PKK Mothers in Bondoyudo Village Lumajang District - Frimha Purnamawati; Nani Sintiawati; Niswatul Imsiyah; Irliana Faiqotul Himmah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Bondoyudo Village, Sukodono District, Lumajang Regency is one of the villages with a variety of potential crops ranging from bananas, tomatoes, vegetables and other fruit crops, not separated from that Bondoyudo Village also has many